THE PARADIGM SHIFT IN CONTRACT INTERPRETATION: A COMPARATIVE ANALYSIS OF INDONESIA, NEW ZEALAND, THE CISG, AND THE UPICC - Mursal Maulana; Jani Purnawanty; Rafan Darodjat; Meliesa Permatahati; Michael Wolff (Indonesia Private Law Review, 2026)
Contract interpretation remains a contested issue in contract law, particularly under the Indonesian Civil Code, which reflects a civil law tradition that prioritizes textual interpretation. Modern commercial practice, however, demands a more contextual approach. This article examines how Indonesia can modernize its interpretive framework through a normative comparative analysis of the Indonesian Civil Code and the contract law of New Zealand, with reference to the United Nations Convention on Contracts for the International Sale of Goods and the UNIDROIT Principles of International Commercial Contracts. The study finds that contemporary contract law has shifted toward an objective contextual approach that preserves the primacy of contractual language while incorporating commercial context, reasonableness, and good faith. Incorporating this approach into the Indonesian Civil Code would enhance interpretive consistency, strengthen judicial reasoning, and provide a principled foundation for contract law reform in Indonesia.